1999
DOI: 10.1103/physrevlett.82.446
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Hole Pair Creation at Ag and Cu Surfaces by Adsorption of Atomic Hydrogen and Deuterium

Abstract: Hot electrons and holes created at Ag and Cu surfaces by adsorption of thermal hydrogen and deuterium atoms have been measured directly with ultrathin metal film Schottky diode detectors on Si(111). When the metal surface is exposed to these atoms, charge carriers are excited at the surface, travel ballistically toward the interface, and have been detected as a chemicurrent in the diode. The current decreases with increasing exposure and eventually reaches a constant value at the steady-state coverage. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
152
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 20 publications
10
152
0
3
Order By: Relevance
“…This analysis is consistent with previous work suggesting that only the H-H recombination reaction on Au produces hot electrons (24) and chemicurrent (13). We also note that the H-adsorption-induced chemicurrents seen by Schottky diode experiments on Ag surfaces (7,11) were performed at a surface temperature (100-135 K) far lower than the H 2 recombinative desorption temperature (∼170 K) (25). Thus, there was no chance that this source of hot electrons could have been seen in those experiments.…”
Section: Significancesupporting
confidence: 81%
See 2 more Smart Citations
“…This analysis is consistent with previous work suggesting that only the H-H recombination reaction on Au produces hot electrons (24) and chemicurrent (13). We also note that the H-adsorption-induced chemicurrents seen by Schottky diode experiments on Ag surfaces (7,11) were performed at a surface temperature (100-135 K) far lower than the H 2 recombinative desorption temperature (∼170 K) (25). Thus, there was no chance that this source of hot electrons could have been seen in those experiments.…”
Section: Significancesupporting
confidence: 81%
“…However, a growing number of examples have been found where electronic and nuclear degrees of freedom are strongly coupled in violation of the BOA (2-6). H-atom interactions at metals offer a remarkable opportunity to test non-BOA theories against experiment, since H-adsorptioninduced chemicurrent experiments (7)(8)(9)(10)(11)(12)(13)(14) offer a direct measure of electronic excitation and H-atom inelastic scattering experiments (15) directly probe nuclear motion. In chemicurrent experiments, exothermic H interactions like adsorption and recombination produce hot electrons that pass over a potential barrier to be collected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 10a, since the work function of metal Au (Φ m = 4.8 eV) is smaller than that of semiconductor TiO 2 (Φ s = 5.1 eV) [70], the electrons can diffuse from the metal into the semiconductor when the two phases are in contact [71,72]. This electron transfer was called "hot-electron flow" [56,57,[73][74][75] or "chemicurrent" [76][77][78], which usually happened in exothermic catalytic reactions [56,57,[73][74][75] and low-energy reactions [74] or even nonthermal directions [75]. For example, it has been reported that electron excitation was also involved in atomic/molecular adsorption processes [73,77,78].…”
Section: Proposed Electron Flow Processmentioning
confidence: 99%
“…1a. Non-catalytic metal-semiconductor diodes have been used to prove that hot electrons are generated in adsorption reactions in ultrahigh vacuum (UHV) at temperatures below 150 K [18][19][20] . By using catalytic metal-semiconductor diodes such as Pt/TiO 2 or Pt/GaN, it has also been possible to detect steady chemicurrent from catalytic CO oxidation at atmospheric pressure, between 400 K and 550 K 16,21 .…”
mentioning
confidence: 99%